Nghiên cứu khả năng bảo vệ chống ăn mòn của lớp phủ epoxy CNT/ZnO-clay nanocompozit - Vũ, Phạm Gia; Xuân Hằng, Tô Thị; Oánh, Vũ Kế; Trúc, Trịnh Anh; Thủy, Thái Thu (Vietnam Journal of Chemistry, 2017)
Mechanical and corrosion protection properties of the epoxy nanocomposite coatings depended on the dispersion of nanoparticles in epoxy matrix. To improve the dispersion of carbon nanotubes zinc oxide (CNT/ZnO) in epoxy matrix composites, clay nanofil8 (N8) was added. Fourier Transform Infrared (FTIR), X-ray diffraction (XRD) Field Emission Scanning Electron Microscope (FE-SEM) analyses show the distribution of CNT/ZnO and clay in epoxy matrix. The electrochemical impedance spectroscopy (EIS) was evaluated the anti-corrosion of epoxy nanocomposite coatings. The mechanical properties such as adhesion, impact and bending strength were also carried out. By using 0.25 % CNT/ZnO combined with 1 % N8 compound, the mechanical and corrosion protection behavior of epoxy composite coatings were improved. Keywords. Carbon nanotube, clay, nano CNT/ZnO, epoxy, nanocomposite, corrossion